Counteracting Fatigue in Multiple Sclerosis with Right Parietal Anodal Transcranial Direct Current Stimulation - Hanken, Katrin; Bosse, Mona; Möhrke, Kim; Eling, Paul; Kastrup, Andreas; Antal, Andrea; Hildebrandt, Helmut (Frontiers in Neurology, 2016)
Background: Fatigue in multiple sclerosis (MS) patients appears to correlate with vigilance decrement as reflected in an increase in reaction time and errors with prolonged time-on-task. Objectives: The aim of this study was to investigate whether anodal transcranial direct current stimulation (tDCS) over the right parietal or frontal cortex counteracts fatigue-associated vigilance decrement and subjective fatigue. Methods: In study I, a randomized double-blind placebo-controlled study, anodal tDCS (1,5mA) was delivered to the right parietal cortex or the right frontal cortex of 52 healthy participants during the first 20min of a 40min lasting visual vigilance task. Study II, also a randomized double-blind placebo-controlled study, investigated the effect of anodal tDCS (1.5mA) over the right parietal cortex in 46 MS patients experiencing cognitive fatigue. TDCS was delivered for 20min before patients performed a 20min lasting visual vigilance task. Results: Study I showed that right parietal stimulation, but not right frontal stimulation, counteracts the increase in reaction time associated with vigilance decrement. Hence, only right parietal stimulation was applied to the MS patients in study II. Stimulation had a significant effect on vigilance decrement in mildly to moderately cognitively fatigued MS patients. Vigilance testing significantly increased the feeling of fatigue independent of stimulation. Conclusions: Anodal tDCS over the right parietal cortex can counteract the increase in reaction times during vigilance performance but not the increase in subjective fatigue. This finding is compatible with our model of fatigue in MS, suggesting a dissociation between the feeling and the behavioral characteristics of fatigue.